Liberal Political Sociability in Tunja: Conlicts, Utopias and Dystopias from 1843-1851 - Vega Torres, Daniel Roberto (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This article reconstructs the experience of the Society of Popular Instruction, as a form of liberal political sociability developed by lawyers and other signiicant individuals in the city between 1843 and 1851. Initially, we present the political conlicts in which these associations were involved during the 1940’s, due particularly to their involvement in provincial and national disputes. Secondly, the formalization of politicalgroups with liberal backing is contextualized as occurring after the consolidation of the movement between 1849 and 1850. Lastly a discursive analysis of the Democratic Society of Tunja is provided with regard to its sense of belonging, strategies, utopias and dystopias, that characterized a liberal proposal in the region in the mid-19th century. It is concluded that the liberal organization in Tunja sought to take advantage of the political situation of the time in order to improve the position ofcertain projects and interests of notable individuals in the city.